Are lung ultrasound features more severe in infants with bronchiolitis and coinfections? - De Rose, Domenico Umberto; Maddaloni, Chiara; Martini, Ludovica; Ronci, Sara; Pugnaloni, Flaminia; Marrocco, Gabriella; Di Pede, Alessandra; Di Maio, Velia Chiara; Russo, Cristina; Ronchetti, Maria Paola; Perno, Carlo Federico; Braguglia, Annabella; et al. (Frontiers in Pediatrics, 2023)
The lung ultrasound (LUS) score can be a useful tool to predict the need for respiratory support and the length of hospital stay in infants with bronchiolitis.Objective: To compare lung ultrasound features in neonates and infants up to three months of age with bronchiolitis to determine whether LUS scores (range 0-36) differ in infants with coinfections or not.Methods: Neonates and infants younger than three months admitted to neonatal units from October 2022 to March 2023, who underwent lung ultrasound evaluation on admission, were included in this retrospective study.We included 60 patients who underwent LUS evaluation at admission. Forty-two infants (70.0 %) had a single viral infection. Eighteen infants (30.0%) had a coinfection: fifteen infants (25.0 %) had more than one virus at PCR; one infant (1.7 %) had both a viral coinfection and a viral-bacteria coinfection; two infants (3.3 %) had viral-bacteria coinfection. Infants with a single viral infection and those with coinfections had similar LUS scores globally and in different lung zones. An LUS score higher than 8 was identified to significantly predict the need for any respiratory support (p= 0.0035), whereas an LUS score higher than 13 was identified to significantly predict the need for mechanical ventilation (p= 0.024).In our small cohort of neonates and infants younger than three months hospitalized with bronchiolitis, we found no statistically significant differences in the LUS score on admission between patients with a single viral infection and those with multiple infections.